The function f is given by f(x) = e^2x-1
- Find the equation for the tangent (don't know if that is the correct word in English) in the spot (1, e)
The answer is: y= 2ex-e
Could anyone show me how to do this? My guess is to first ... ehm, derivate (??) it? You know:
f(x) = e^2x-1
f ' (x)= 2x * e^2x-1 <---- if that is correct, I don't know how to proceed further.
- Find the equation for the tangent (don't know if that is the correct word in English) in the spot (1, e)
The answer is: y= 2ex-e
Could anyone show me how to do this? My guess is to first ... ehm, derivate (??) it? You know:
f(x) = e^2x-1
f ' (x)= 2x * e^2x-1 <---- if that is correct, I don't know how to proceed further.